General Election Law Position In The Enforcement Of Criminal Law - Eko Nuryanto; Gunarto Gunarto (Law Development Journal, 2020)
The aim in this study, to find out and analyze the mechanism for law enforcement of election criminal acts based on the General Election Law. In this research, the writer used sociological juridical method with the research specification in the form of descriptive analysis. The data used for this research are primary and secondary data. Based on the results of research that concludes, namely the mechanisms in the election criminal justice process based on Act No. 7 of 2017 concerning Elections through investigations in Article 479, investigations in Article 480 paragraph 1, prosecution in Article 480 paragraph 4, and court in Article 481 paragraph 1 The District Court exercises the authority to examine, adjudicate, and decide on cases where the process is carried out in a special court which still refers to the stages of the general criminal justice process in the Criminal Procedure Code.